2019
DOI: 10.1080/20477724.2019.1595904
|View full text |Cite
|
Sign up to set email alerts
|

Malaria epidemiology and comparative reliability of diagnostic tools in Bannu; an endemic malaria focus in south of Khyber Pakhtunkhwa, Pakistan

Abstract: The present study was aimed at elucidation of malaria epidemiology and comparing performance of several diagnostic procedures in Bannu, a highly endemic district of Khyber Pakhtunkhwa, Pakistan. Dried blood spots were collected from patients suspected of malaria visiting a hospital and two private laboratories in district Bannu and processed for species-specific PCR (rRNA). Patients were also screened for malaria through microscopy and RDT. A well-structured questionnaire was used to collect patient informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…The results of an individual study demonstrated that 18 studies in total 19 , 21 , 26 , 30 , 31 , 34 36 , 40 43 , 46 51 had identical results for RDT and microscopy. Six studies 19 , 30 , 31 , 35 , 40 , 47 gave identical results for RDT type 3 and microscopy. Two studies 41 , 51 gave identical results for RDT type 2 and microscopy.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…The results of an individual study demonstrated that 18 studies in total 19 , 21 , 26 , 30 , 31 , 34 36 , 40 43 , 46 51 had identical results for RDT and microscopy. Six studies 19 , 30 , 31 , 35 , 40 , 47 gave identical results for RDT type 3 and microscopy. Two studies 41 , 51 gave identical results for RDT type 2 and microscopy.…”
Section: Resultsmentioning
confidence: 66%
“…Among the 28 articles included in the present study, 3 reported mixed infections by RDT type 2 (pf-HRP2/pan-aldolase) and microscopy 27 , 41 , 51 , 13 by RDT type 3 (pf-HRP2/pan-pLDH) and microscopy 19 , 21 , 27 , 28 , 30 , 31 , 33 , 35 , 38 , 40 , 43 , 44 , 47 , 3 by type 4 (Pf-LDH/pan-pLDH) and microscopy 34 , 36 , 51 , 1 by RDT type 5 (Pf/Pv-pLDH) 46 , and 9 by RDT type 6 (pf-HRP2/Pv-pLDH) 21 , 26 , 36 , 42 , 43 , 46 , 48 – 50 . Among 27 articles included in the present study, 1 reported mixed infections by RDT type 2 and PCR 32 , 5 on RDTs type 3 and PCR 21 , 28 , 33 , 43 , 45 and 5 by RDT type 6 and PCR 21 , 26 , 29 , 37 , 43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latest WHO report projected nearly 700,000 malaria cases in Pakistan in 2019 [ 4 ]. A recent study in the highly endemic Bannu District in Pakistan examined blood smears of 2033 individuals suspected of malaria infection and reported 429 (21.1%) malaria-positive cases by at least one diagnostic test (microscopy, rapid diagnostic test, RDT or PCR) [ 75 ]. The positivity by PCR, microscopy and RDT was 30.5%, 17.7% and 16.4%, respectively.…”
Section: Epidemiological Data From Countries Of Origin For Importementioning
confidence: 99%